2018
DOI: 10.1590/fst.18217
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of β-glucan of Hericium erinaceus, Avena sativa L., and Saccharomyces cerevisiae and in vivo evaluation of their immunomodulatory effects

Abstract: Beta-glucan (BG) is one of the most common types of polysaccharides, and is a potent immune activator. Ot is present in microbes, plants, and mushrooms. The immunomodulatory properties of BG are varied among different species. This paper explains the composition of BG from yeast (Saccharomyces cerevisiae HOO31), oat (Avena sativa L.) and mushroom (Hericium erinaceus), and also describes in vivo immunomodulation and changes in the antioxidant capacity of BG. In vivo studies were conducted in BALB/cMlac mice, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The authors suggested oat b-glucans have strong antiinflammatory potential, and it could be proposed for intestinal inflammatory disease patients (Wilczak et al, 2015). Chaiyasut et al (2018) compared the immunemodulatory activity of three b-glucan sources, that is yeast, mushroom and oat through an in vivo study. Yeast b-glucan stimulated the expression of IL-6, IL-17, IFN-c, IL-10 and TGF-b more effectively than oat and mushroom ones.…”
Section: Colon Cancer Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested oat b-glucans have strong antiinflammatory potential, and it could be proposed for intestinal inflammatory disease patients (Wilczak et al, 2015). Chaiyasut et al (2018) compared the immunemodulatory activity of three b-glucan sources, that is yeast, mushroom and oat through an in vivo study. Yeast b-glucan stimulated the expression of IL-6, IL-17, IFN-c, IL-10 and TGF-b more effectively than oat and mushroom ones.…”
Section: Colon Cancer Protectionmentioning
confidence: 99%
“…↑ THP-1 macrophages ↓ pro-inflammatory cytokines (IL-6, IL-8, IL-1b) Arena et al (2016). Yeast b-glucan has higher immunomodulatory effect than oat b-glucanChaiyasut et al (2018)…”
mentioning
confidence: 99%
“…β-Glucan from the mushrooms was extracted following the method of Chaiyasut et al [13] with some modifications. Fresh fruiting body of mushroom was washed in deionised water, sliced and dried out in a hot air oven at 36 °C for 11 h. Ground dried mushrooms were dissolved in NaOH (1 M) and heated at 80 °C for 6 h. This was followed by centrifugation (6000× g ) at 4 °C for 25 min and pellet was washed with deionised water thrice and re-centrifugated to separate compounds such as heteropolysaccharides, phenols and glycogen.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. (2A), shows that the band range of ~1027.99 cm -1 is a characteristic feature of polysaccharides and assigned for β-1,4 glucans (17) , the absorbance peak at this band represent the existence of C-O-C group (18) . In addition, hydroxyl groups and carboxyl groups were detected at band 2923.88 cm -1 , these groups are features of carbohydrate structure (19) .…”
Section: Resultsmentioning
confidence: 98%